Rachel Gerhardt’s Anxiety and Defense Mechanism Portrayed in Ruth Ware’s The Turn of The Key - Billy Ikhlas Mulia; Tri Pramesti (Fakultas Ilmu Budaya Universitas 17 Agustus 1945 Surabaya, 2023)
This study aims to examine the anxiety and defense mechanisms of Rachel Gerhardt in Ruth Ware's The Turn of the Key. The purpose of this study is to analyze Rachel Gerhardt's types of anxiety and then establish which defense mechanism Rachel Gerhardt uses. This research is performed because anxiety always occurs in everyday life and subconsciously employs defense mechanisms to overcome the anxiety. The data source of this study is the novel The Turn of The Key by Ruth Ware. The method applies in this research is the descriptive qualitative method. This study uses the theory of psychoanalysis and defense mechanisms by Sigmund Freud. This study uses a psychological approach because it applies psychoanalytical theory and aims to reveal how the subconscious expression works, especially the defense mechanism. Based on the analysis, it can be concluded that Rachel experiences three types of anxiety: realistic anxiety, neurotic anxiety, and moral anxiety. Rachel uses eight defense mechanisms, such as rationalization, sublimation, reaction formation, regression, displacement, projection, introjection, and fixation, to relieve the anxiety that Rachel experience.